STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM PEMBINAAN NILAI-NILAI RELIGIUS DI LINGKUNGAN MADRASAH ALIYAH MUSLIM CENDIKIA BENGKULU TENGAH - Dewi Ratna Furi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2019)
The  study  aims  to  find out  the  strategy  of Madrasah principal  education in the  fostering  of religious  values  in Madrasah Aliyah Muslim Cendikia  Bengkulu  Tengah, responses and  funds  of Madrasah shareholders in the  development of religious values,  as well as factors anything  that becomes a role in the fostering of religious values in the madrasah Aliyah Muslim Cendikia  Bengkulu  Tengah. This research  uses qualitative  descriptive  method. The research  data  were collected using interview,  observation and  documen techniques. The data  collected  from the technique is analyzed  by using data  reduction, data  presentation and  data  verification,  data  validity is obtained by using data  triangulation. The results of this study indicate that leadership strategy of head  master in religious values development in Islamic madrasah Aliyah Cendikia  Bengkulu Tengah used  several strategies  such as: habituation strategy,  exemplary  strategy and  partnership strategy.  In the guidance of religious values in madrasah, madrasah stake holders respond  positively to the head  master  by demonstrating their respective  commit- ments.  The inhibiting or temptation factor in religious values in Madrasah Aliyah Muslim Cendikia  from the basic education of diverse teachers  and facilities and infrastructure that has not been  maximized.  The final Conclusion can be stated that the head master  strategies  in guiding islamic religious values at Madrasah Aliyah Muslim Cendikia  have  positive findings For madrasah stakeholders.